Resilience and survivability in MANET: Discipline, issue and challenge - Azni, A.H; Ahmad, Rabiah; Azri, Zul (2011)
The wireless technology has become essential part in modern life, and thus the consequences of network disruption is becoming severe.It is widely known that wireless network is not sufficiently resilience, survive and dependable and significant research and development is necessary to improve the situation. This paper provide a survey of vast disciplines in MANET, a resilience strategy is also presented on how to defend, detect and countermeasures malicious node. Current issues and challenges to achieve resilience and survivability is also presented for future direction.